Formation of the chromosomal and microsatellite instabilities in blood cells of cancer patients under the combined exposure in vitro to ionizing radiation and co-mutagens - Domina, E.A.; Ivankova, V. S.; Pylypchuk, O.P.; Zelena, L.B. (Reports of the National Academy of Sciences of Ukraine, 2015)
This work presents the first studies of the quantitative and qualitative patterns of genome instability formation in irradiated somatic cells of cancer patients under the influence of a co-mutagen ascorbic acid. Depending on the drug concentration, the co-mutagenic effects were revealed as an increased frequency of chromosomal aberrations by 1.4–1.7 times due to the repair system repression. The obtained results should be taken into account in the radiation oncology for the control over comutagenic drug prescriptions to the patient to prevent the development of secondary tumors.